2001
DOI: 10.1109/8.947016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured and predicted time dispersion and direction of arrival for multipath in a small cell environment

Abstract: A number of three-dimensional (3-D) direction-of-arrival measurements in a small campus environment at 1845 MHz are described. The impulse responses and the power have been measured using an 80-MHz wide-band receiver applying correlation techniques. These measurements are compared with theoretical predictions made with a site-specific ray-based propagation predictor tool to determine the coherently reflected part of the signal. Furthermore, radiosity is applied as a model to determine the power scattered by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…The room dimensions are width 11 m, length 19 m and height 2.5 m. Segment size has been chosen 0.5 × 0.5 m and the timestep ∆t is 2 ns, obeying (4) in the corners. Transmitter location is at (x Tx ,y Tx ) = (2,6) near the left wall and receiver locations are (x Rx ,y Rx ) = (4,6), (8,6), (12,6), (16,6). In all instances, the z (vertical, height) coordinates are 1.5 m. The coordinate origin (x,y,z) = (0,0,0) is at the lower left corner.…”
Section: Numerical Examplementioning
confidence: 99%
“…The room dimensions are width 11 m, length 19 m and height 2.5 m. Segment size has been chosen 0.5 × 0.5 m and the timestep ∆t is 2 ns, obeying (4) in the corners. Transmitter location is at (x Tx ,y Tx ) = (2,6) near the left wall and receiver locations are (x Rx ,y Rx ) = (4,6), (8,6), (12,6), (16,6). In all instances, the z (vertical, height) coordinates are 1.5 m. The coordinate origin (x,y,z) = (0,0,0) is at the lower left corner.…”
Section: Numerical Examplementioning
confidence: 99%
“…Both 2-D and 3-D [7][8][9][10][11][12][13][14][15][16], ray tracers have been proposed in the case of urban propagation, similarly for indoor propagation [17][18][19][20][21]. Moreover, to overcome the lack of diffuse radiation due to the roughness of the surfaces ray tracing techniques have been recently improved resorting to diffuse scattering models [22] and radiosity [23]. To improve the computational efficiency instead, some of the proposed algorithms exploit geometrical symmetries, such as vertical symmetry for urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that various urban scenarios with specific peculiarities of the topography influence in different manners on the mutual AOA, EOA, and TD distributions of the total signal [20]- [22], [31]- [38], [43]. From the point of view of designing multiple access networks, it is very important to use some unified spatio-temporal approach for various situations in the urban scene.…”
mentioning
confidence: 99%